El sindicalismo socialista Español : aproximación oral a la historia de UGT (1931-1975) / [autores, Alicia Alted Vigil ... et al.] ; Presentación Jesús Pérez Martínez; Introducción Manuela Aroca Mohedano - Alted Vigil, AliciaPérez Martínez, JesúsAroca Mohedano, Manuela
Bibliografía: p. 399-401. Índice